Expansion of the neurodevelopmental phenotype of individuals with EEF1A2 variants and genotype-phenotype study - Paulet, Alix; Bennett-Ness, Cavan; Ageorges, Faustine; Trost, Detlef; Green, Andrew; Goudie, David; Jewell, Rosalyn; Kraatari-Tiri, Minna; PIARD, Juliette; Coubes, Christine; Lam, Wayne; Lynch, Sally Ann; et al. (European Journal of Human Genetics, 2024)
Translation elongation factor eEF1A2 constitutes the alpha subunit of the elongation factor-1 complex, responsible for the enzymatic binding of aminoacyl-tRNA to the ribosome. Since 2012, 21 pathogenic missense variants affecting EEF1A2 have been described in 42 individuals with a severe neurodevelopmental phenotype including epileptic encephalopathy and moderate to profound intellectual disability (ID), with neurological regression in some patients. Through international collaborative call, we collected 26 patients with EEF1A2 variants and compared them to the literature. Our cohort shows a significantly milder phenotype. 83% of the patients are walking (vs. 29% in the literature), and 84% of the patients have language skills (vs. 15%). Three of our patients do not have ID. Epilepsy is present in 63% (vs. 93%). Neurological examination shows a less severe phenotype with significantly less hypotonia (58% vs. 96%), and pyramidal signs (24% vs. 68%). Cognitive regression was noted in 4% (vs. 56% in the literature). Among individuals over 10 years, 56% disclosed neurocognitive regression, with a mean age of onset at 2 years. We describe 8 novel missense variants of EEF1A2. Modeling of the different amino-acid sites shows that the variants associated with a severe phenotype, and the majority of those associated with a moderate phenotype, cluster within the switch II region of the protein and thus may affect GTP exchange. In contrast, variants associated with milder phenotypes may impact secondary functions such as actin binding. We report the largest cohort of individuals with EEF1A2 variants thus far, allowing us to expand the phenotype spectrum and reveal genotype-phenotype correlations.
CRIS-Team Scopus Importer:2024-09-13